Biocatalytic Feedback‐Driven Temporal Programming of Self‐Regulating Peptide Hydrogels. Issue 45 (6th August 2015) - Heuser, Thomas; Weyandt, Elisabeth; Walther, Andreas
Abstract: Switchable self‐assemblies respond to external stimuli with a transition between near‐equilibrium states. Although being a key to present‐day advanced materials, these systems respond rather passively, and do not display autonomous dynamics. For autonomous behavior, approaches must be found to orchestrate the time domain of self‐assemblies, which would lead to new generations of dynamic and self‐regulating materials. Herein, we demonstrate catalytic control of the time domain of pH‐responsive peptide hydrogelators in a closed system. We program transient acidic pH states by combining a fast acidic activator with the slow, enzymatic, feedback‐driven generation of a base (dormant deactivator). This transient state can be programmed over orders of magnitude in time. It is coupled to dipeptides to create autonomously self‐regulating, dynamic gels with programmed lifetimes, which are used for fluidic guidance, burst release, and self‐erasing rapid prototyping. Abstract : Programmed to self‐destruct : An internal enzymatic feedback system enables the autonomous self‐regulation over time of a pH‐responsive peptide gelator (see picture; SA=self‐assembly). The resulting dynamic hydrogels with programmed lifetimes are suitable for application in fluidic guidance, burst release, and transient rapid prototyping.